Validation of an MRI Technique for the 6-DOF Knee Kinematics Measurement - Tang, Shixiong; Zheng, Liwen; Luo, Yongheng; Wu, Ren; Tian, Qunyan; Wang, Lei (Frontiers in Bioengineering and Biotechnology, 2022)
Background: For total knee arthroplasty (TKA), the optimal rotational position of the femoral component is felt to be critically important, but the current knee joint kinematics measurement technology is unable to identify the accurate rotation axis of the knee joint. Purposes: (1) To propose a method for measuring knee joint kinematics and verify its accuracy; (2) To propose a method for determining the optimal rotation axis of knee joint for TKA surgery, based on accurate kinematic measurement results. Materials and methods: In vitro, aquarium stones and goniometer/vernier caliper were immersed in water to capture MRI images. In vivo, 36 healthy elderly participants (22 Female, 14 Male) were recruited from the local community. Our method was employed to measure the relative motion of the aquarium stones/bones. Results: In vitro, all measurements were accurate to <1mm and <1°. In vivo, all knee measurements showed roll back motion and screw home motion. Conclusion: In the application scenario of knee joint kinematics measurement, our method has a measurement accuracy of <1° of rotation angle and <1mm of reference point displacement, and it can be employed to identify the optimal rotation axis of the knee joint for TKA surgery.